2017
DOI: 10.1038/ijo.2017.234
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific association between body mass index and depression: The Korea National Health and Nutrition Examination Survey 2014

Abstract: We found that overweight and mild obesity significantly lowered the risk of depression in elderly adults. These findings suggest that mild increases in BMI beyond the normal range may be a protective factor for depression in elderly Korean adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
1
15
3
Order By: Relevance
“…However, there was an insignificant positive association between underweight and depression in general adults in Mainland China. Our results are inconsistent with the estimates reported in Japan, Korea, and Taiwan ( 30 , 13 , 35 , 36 ). These trends can be observed in different age populations, and underweight elderly adults are far more likely to be depressed ( 30 , 13 , 35 , 36 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, there was an insignificant positive association between underweight and depression in general adults in Mainland China. Our results are inconsistent with the estimates reported in Japan, Korea, and Taiwan ( 30 , 13 , 35 , 36 ). These trends can be observed in different age populations, and underweight elderly adults are far more likely to be depressed ( 30 , 13 , 35 , 36 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are inconsistent with the estimates reported in Japan, Korea, and Taiwan ( 30 , 13 , 35 , 36 ). These trends can be observed in different age populations, and underweight elderly adults are far more likely to be depressed ( 30 , 13 , 35 , 36 ). Yet, the common population tends to have a distortion of body weight, which entitles thinness as a beauty symbol owing to social standard ( 37 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…21 Interestingly, a further study also found that obesity and depression may be inversely proportional in men. 22 Recent data from a large longitudinal study by Oh et al 23 There are many possible explanations for the findings of this study. First, lifestyle factors are likely to play a large role in the association observed.…”
Section: Adjusted Rates Of Depressionmentioning
confidence: 80%
“…Recent data from a large longitudinal study by Oh et al has also found that an overweight status (BMI 25‐29.99 kg/m 2 ) and mild obesity (BMI 30‐35 kg/m 2 ) were in fact protective against depression. This is in line with some previous findings that have led to an alternative hypothesis that a “U” shaped relationship between BMI and depression may exist.…”
Section: Discussionmentioning
confidence: 93%